Avoiding Debt Traps Financial Backstops and Structural Reforms - Padoan, Pier Carlo (OECD Publishing, 2012)
In this paper we develop a simple analytical framework to analyze "good" and "bad equilibria" in public-debt and growth dynamics. The "bad equilibrium" is characterised by the simultaneous occurrence, and adverse feedbacks between, high and growing fiscal deficits and debt, high risk premia on sovereign debt, slumping economic activity and plummeting confidence, whereas a "good equilibrium" is characterized by stable growth and debt and low risk premia. We use this framework to identify - both theoretically and empirically - the good and bad equilibrium levels of debt and policies that can help a country caught in a bad equilibrium to recover. The analysis shows that despite some output loss in the short run fiscal consolidation can help countries escape from the bad equilibrium trap. More broadly, we find that a combination of financial backstops, structural reform and fiscal consolidation is most effective in helping countries getting onto a sustainable path
Keywords: Economics